An Analysis of Narrative Time in The Translation of Tārīkh-e Yamīnī based on Gerard Genet's Perspective - Mohadeseh Ghooshe; Davood Mohammadi; Seyed Hasan Tabatabaei (مطالعات زبانی و بلاغی)
: As an emerging area in literary criticism, the study of narrative time has attracted narratologists’s attention since the 20th century. One of the figures focusing on the analysis of time in narrative is Gerard Genet, who believes that the time of story and narration are not parallel but different, due to three reasons; order or chronological sequence, duration or temporal continuity, and frequency or repetition. The Translation of Tārīkh-e Yamīnī is one of the old texts in the field of historiography, which chronicles the events of Samanid and Ghaznavid eras. As it is written in the form of successive narrative fragments, with the author employing various techniques of temporal manipulation, it can be analyzed in terms of narrative time. This study examined the use of time through an inductive reasoning approach, focusing on order, duration and frequency. The result demonstrates that, although this work falls into the category of realistic and historical writings, the author has skillfully employed various narrative time techniques. Its refined prose style ensures that prolonged descriptions remain engaging rather than tedious. Moreover, the author’s seamless blending of historiography and realism is evident.